Wstrzemięźliwość czy promiskuityzm? Analiza zachowań seksualnych polskich singielek i singli = Abstinence or promiscuity? Analysis of sexual risk behaviours of Polish single men and women - Izdebski, Zbigniew (1956- ); Paprzycka, Emilia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Sex life of single men and women is an issue overlooked by the researches dealing with the description of this social category but the one that is present in the social consciousness in the form of opposite stereotypes. Women living alone are perceived either as unattractive, asexual and unwanted, or as so called liberated women - very liberal in terms of sex life.
Keywords: single life; single women; single men; sexual behaviour; risky sexual behaviours; single; zachowania seksualne; zachowania ryzykowne